Interoperability between health information systems - Fernandes, J.; Jerónimo, C.; Pereira, L.; Dias, Á.; Lopes da Costa, R.; Gonçalves, R. (Sustainability in software engineering and business information management. Lecture Notes in Information Systems and Organisation, 2023)
In the health system, the adoption of Informatic and Communications Technologies (ICTs) are becoming visible, with more heterogeneity and interoperability between Information Systems (IS) and medical data. The technological revolution enhances interoperability between Health Information Systems (HIS) as a new challenge to achieve sustainability. Thus, this study aims to explore and analyse the communication between information systems in Portuguese hospitals. This study follows qualitative research, sixteen semi-structured interviews were conducted with healthcare professionals and hospital suppliers to collect their experience on interacting with HIS, the stakeholders’ role, and the measures that are considered crucial to improve the current paradigm. The subsequent analysis was supported with the MAXQDA program to organize and identify the interviewees’ keywords, explanations, and views. The key findings of the study were the inadaptation of public hospitals’ board to manage HIS and promote sustainability, the importance that healthcare professionals have in the implementation of new HIS in hospitals and the lack of interoperability between the systems resulting in slower and complex navigation for the user. To achieve successful interoperability between HIS, hospitals need to have a clear hospital strategy focused on the digitalization of processes. Providing an IT structure that supports the implementation and management of the systems, managing the relationship with the hospital’s suppliers, and encouraging the healthcare professionals to involve and use this technology. Further research needs to consider a larger sample and other research methods to identify new constraints and opportunities about this topic.